2007
DOI: 10.1534/genetics.106.066258
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Mapping of Recombination Hotspots in Human Immunodeficiency Virus via Spatially Smoothed Change-Point Processes

Abstract: We present a Bayesian framework for inferring spatial preferences of recombination from multiple putative recombinant nucleotide sequences. Phylogenetic recombination detection has been an active area of research for the last 15 years. However, only recently attempts to summarize information from several instances of recombination have been made. We propose a hierarchical model that allows for simultaneous inference of recombination breakpoint locations and spatial variation in recombination frequency. The dua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 59 publications
(56 reference statements)
0
37
0
Order By: Relevance
“…The identification of recombination breakpoints in viruses is useful to detect circulating recombinant forms (Minin et al, 2007;Archer et al, 2008), to study adaptive recombination (Monjane et al, 2011), to analyze recombinant data (Kosakovsky Pond et al, 2006a;Arenas and Posada, 2010c;Arenas, 2013b), and to infer the underlying mechanisms of recombination. Recombination is generally non-homogeneous along genomes (Minin et al, 2007;Monjane et al, 2011). A number of programs exist to detect recombination breakpoints (Martin et al, 2011a,b), but some of them are more commonly used because of their high accuracy and user-friendly environment.…”
Section: Inference Of Recombination Breakpointsmentioning
confidence: 99%
“…The identification of recombination breakpoints in viruses is useful to detect circulating recombinant forms (Minin et al, 2007;Archer et al, 2008), to study adaptive recombination (Monjane et al, 2011), to analyze recombinant data (Kosakovsky Pond et al, 2006a;Arenas and Posada, 2010c;Arenas, 2013b), and to infer the underlying mechanisms of recombination. Recombination is generally non-homogeneous along genomes (Minin et al, 2007;Monjane et al, 2011). A number of programs exist to detect recombination breakpoints (Martin et al, 2011a,b), but some of them are more commonly used because of their high accuracy and user-friendly environment.…”
Section: Inference Of Recombination Breakpointsmentioning
confidence: 99%
“…Little is known about the selective forces that drive viral evolution in natural ecosystems, which contrasts with the more detailed population genetics studies in crop plants that have revealed the importance of mutation rates [36,37], recombination [38][39][40], genetic drift [1 ], and, to a lesser extent, migration in virus evolution. In recent years, the methodology of phylogenetic inference, relying on maximum likelihood, Bayesian and other quantitative frameworks, has made great strides and started to unravel life histories of viruses with a sensitivity not attainable previously [36,[41][42][43][44][45][46]. Approaches based on the coalescent theory and other statistical models have been developed [47][48][49], allowing investigators to quantify the effects of the individual evolutionary factors, including particularly revealing results on positive vs. purifying selection, interhost vs. intrahost evolution patterns, etc.…”
Section: Phylogenetic Approaches To Study Virus Emergence Evolution mentioning
confidence: 99%
“…This novel finding creates an opportunity, as well as poses a challenge, for molecular geneticists in the further exploration of the relationship between fine structure and crossover frequency of rice chromosomes by dissecting the mechanism of high recombination frequencies in the four regions surrounding the gw-5 gene between the two parents (Asominori and CSSL28). Similarly, linkage mapping strategies have been used to investigate the recombination hotspots on chromosomes of a wide variety of organisms, e.g., wheat (Faris et al 2000), neurospora (Yeadon et al 2004), mouse (Kelmenson et al 2005), and human (Minin et al 2007). …”
Section: Dissection Of the Genetic Modes Of Qtl Underlying Complex Qumentioning
confidence: 99%